Sense of Unity and Self-Reported Health Among 15-year-Olds: Findings From the Swedish 2017/18 Health Behavior in School-Aged Children Study - Joakim Wahlström; Bitte Modin; Johan Svensson; Petra Löfstedt; Sara Brolin Låftman (Frontiers Media S.A., 2021)
Objectives: Sense of unity refers to the positive feeling of being part of a larger social structure. This study aimed to investigate to what extent adolescents report sense of unity and if this differs across groups, and to assess the associations between sense of unity and self-reported health while taking into account sociodemographic characteristics and tangible social relationships.Methods: Data were obtained from the 2017/18 Swedish Health Behavior in School-aged Children study, using information collected among 15-year-old students (n = 1,392). Linear and binary logistic regression analyses were performed.Results: The participants reported overall high levels of sense of unity. Sense of unity did not differ by gender, but adolescents without an immigrant background and those with higher family affluence reported higher levels. Sense of unity was inversely associated with psychological complaints, somatic complaints, and less than good self-rated health, even when adjusting for sociodemographic characteristics and family, classmate, and teacher relationships.Conclusion: This study suggests that sense of unity may be an important social determinant for adolescent health. More research is needed on the origins and implications of sense of unity.